Susceptibility of three breeds of Ugandan goats to experimental infection with Trypanosoma congolense - Katunguka-Rwakishaya, E.; Murray, M.; Holmes, P.H. (Springer, 1997)
This study has indicated that differences in susceptiblity to Trypanosoma congolense infection exist among the 3 main breeds of goats in Uganda namely, Kigezi, Mubende and small East African (SEA). The Kigezi goats appeared to be the most susceptibe suffering more severe anaemia, greater retardation of growth and more deaths than the other 2 breeds following experimental infection with Trypanosoma congolense. The Small East African goats appeared to be the least susceptible. Following treatment after 84 days of infection, the SEA goats responded much better than the other 2 breeds. By 4 weeks after treatment with diminazene aceturate, the packed cell volume of the Mubende and kigezi-goats were still much lower than those of control animals.